Fault-Tolerant Multilevel Converter to Feed a Switched Reluctance Machine - Pires, Vítor Fernão (2022)
Funding Information: Funding: This research was funded by FCT Funda?ão para a Ciência e a Tecnologia grant number UID/CEC/50021/2020 and UID/EEA/00066/2020. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.